Dynamics of rubber expansion in Lao PDR: policy making under uncertainty - Bouahom, B.; Alberny, E.; Douangsavanh, L.; Castella, J.C. (2011)
The government of Laos long term policy is aiming at reducing rural poverty and stabilize shifting cultivation by creating permanent job for local people, in order to increase forest cover while avoiding negative impacts on deforestation. The overnment of Laos promotes foreign investment in developing tree plantation to increase income sources for rural households and for government as export earnings. The rubber has been seen as a miracle crop, liable to transform the landscapes and rural livelihoods. Within a few years, the rubber industry has become an important sector in the Lao economy thanks to high market demand. The research was designed to provide knowledge that is relevant to policy making in the current context of rubber expansion in Laos, to characterize rubber-based production systems and to understand the conditions of emergence of different types of rubber regimes (smallholder, contract farming and concession). The study sites were selected in seven villages of three different districts namely Sangthong district, Nalae district and Thakeak district. Our analysis of the ‘rubber boom’ started with a literature review, followed by series of meeting with key stakeholders and surveys with local leaders and villagers based on semistructured questionnaire. The study points out important challenges related to the management of agricultural diversity and information available to the various stakeholders. Local farmers face great uncertainty in relation with all aspects of rubber production: i.e. technical, economical, ecological. Integrated planning of resources use is currently being developed to address the complexity of the rubber socio-technical system. Analysis developed along hisresearch showed that the information provided to the decision-makers and village communities should be improved and impact of the rubber expansion on landscapes and livelihoods should be monitored carefully.